Anion‐cation double‐substitution endows iron sulfide with remarkably enhanced specific capacity and rate performance as anode for supercapacitors - Yiwei Yao; Jinsong Wang; Xiaohan Ban; Chi Chen; Qian Wang; Kai Zhu; Ke Ye; Guiling Wang; Dianxue Cao; Jun Yan (EcoMat, 2023)
Abstract Metal sulfides have shown great potential as the anodes of the asymmetric supercapacitors ascribed to their superior theoretical specific capacitance. However, their specific capacitance and rate performances are still far from the expectation due to the intrinsic poor electronic conductivity and sluggish kinetics. Herein, we employ the anion and cation double‐substitution strategy to prepare iron sulfide nanoparticles on graphene composite (denoted as NiFeSP/G) to improve the electronic conductivity of FeS2. The NiFeSP/G composite exhibits greatly improved electrochemical performances with a high specific capacity of 765 C g−1 (765 F g−1) at 5 A g−1 and a remarkable rate capability of 65% at 100 A g−1. Moreover, an aqueous asymmetric supercapacitor is fabricated with the NiFeSP/G as anode and NiCo‐LDH/graphene as cathode presents an impressively high energy density up to 109 Wh kg−1 at 1591 W kg−1 and cycling performance (89% of the initial capacity retained after 8000 cycles).